Advancing ulcerative colitis therapy: a review of 5-ASA synergy with traditional Chinese medicine and natural bioactive compounds - Dong, Weiwei; Wu, Hengquan; Liu, Tao; He, Wenting (Frontiers in Pharmacology, 2026)
5-Aminosalicylic acid (5-ASA) is a first-line drug for the treatment of mild to moderate ulcerative colitis (UC), yet its monotherapy efficacy remains limited. In recent years, the combination of 5-ASA with bioactive components of traditional Chinese medicine (TCM) has emerged as an important strategy in UC management. Studies have shown that natural bioactive compounds from TCM (e.g., berberine, curcumin) contribute to synergistic anti-inflammatory and antioxidant effects, as well as enhanced drug-targeted delivery, while TCM formulations (e.g., Gegen Qinlian Decoction, Xilei San) exert holistic multi-target regulation by inhibiting key inflammatory pathways such as nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK), modulating gut microbiota composition, and restoring mucosal barrier function. This combination strategy significantly improves clinical response rates, endoscopic remission, and mucosal healing, without increasing the risk of adverse effects. It reflects a modern treatment philosophy of “Western medicine for primary action, Chinese medicine for synergistic support,” and provides a safe and effective evidence-based approach for optimizing UC therapy.